(untitled) (Iranian Journal of Kidney Diseases, 2019)
Introduction. Whether administrating of vitamin D supplements increases the risk of hypercalciuria is still unanswered. The aim of the present study was to determine whether use of vitamin D supplementation might increase the risk of hypercalciuria. Methods and Materials. This interventional study was conducted on 30 who suffered from vitamin D insufficiency and deficiency and also had a history of nephrolithiasis. The patients were treated with vitamin D supplement (50000 units per week for 2 months and then every 2 weeks until the end of the 3rd month). Serum and urinary biomarkers were measured at baseline and 3 months after start of vitamin D therapy. Results. Administrating vitamin D supplement for 3 months led to a significant increase in serum level of 25-hydroxyvitamin D from 10.4 ± 4.2 ng/mL to 44.0 ± 10.7 ng/mL (P < .001). Also, the median level of serum parathyroid hormone was significantly reduced from 53 ng/L (interquartile range, 22 ng/L to 163 ng/L) to 38 ng/L (interquartile range, 16 ng/L to 102 ng/L; P < .001). There was also a significant increase in urinary citrate after using vitamin D supplement compared with the baseline from 341 mg (interquartile range, 90 mg to 757 mg) to 411 mg (interquartile range, 115 mg to 1295 mg; P = .045). Comparing biochemical parameters between the groups who developed 15% and greater and less than 15% increase in urinary calcium showed no significant difference after treatment. Conclusions. The use of vitamin D supplements in conventional dose in patients with vitamin D deficiency may not lead to increased risk of hypercalciuria.